Impact of Employee Competence and Loyalty on Job Promotion: An SEM-PLS Approach - Teguh Iman Santoso; Muhammad Nurwaskita Alamsyah (International Journal of Islamic Business and Management Review, 2024)
This study explores the impact of employee competence and loyalty on job promotion outcomes in the context of Indonesia's manufacturing sector. It investigates how these factors interact and influence promotion decisions, drawing on theories such as social exchange theory and the resource-based view. The findings reveal that while competence is a critical determinant of job performance, loyalty significantly enhances an employee's chances of promotion by increasing their visibility and perceived value within the organization. The study also provides practical recommendations for HR departments, emphasizing the importance of training programs, recognition systems, and supportive organizational cultures. These insights contribute to the ongoing debate on the role of competence and loyalty in career advancement. Despite some limitations, including its focus on a single industry, the study paves the way for future research to expand on these findings and explore the dynamics of competence and loyalty across different industries and regions.